Manual Dexterity in Schizophrenia—A Neglected Clinical Marker? - Térémetz, Maxime; Carment, Loïc; Brénugat-Herne, Lindsay; Croca, Marta; Bleton, Jean-Pierre; Krebs, Marie-Odile; Maier, Marc A.; Amado, Isabelle; Lindberg, Påvel G. (Frontiers in Psychiatry, 2017)
Impaired manual dexterity is commonly observed in schizophrenia. However, a quantitative description of key sensorimotor components contributing to impaired dexterity is lacking. Whether the key components of dexterity are differentially affected and how they relate to clinical characteristics also remains unclear. We quantified the degree of dexterity in 35 stabilized patients with schizophrenia and in 20 age-matched control subjects using four visuomotor tasks: (i) force tracking to quantify visuomotor precision, (ii) sequential finger tapping to measure motor sequence recall, (iii) single-finger tapping to assess temporal regularity, and (iv) multi-finger tapping to measure independence of finger movements. Diverse clinical and neuropsychological tests were also applied. A patient subgroup (N = 15) participated in a 14-week cognitive remediation protocol and was assessed before and after remediation. Compared to control subjects, patients with schizophrenia showed greater error in force tracking, poorer recall of tapping sequences, decreased tapping regularity, and reduced degree of finger individuation. A composite performance measure discriminated patients from controls with sensitivity = 0.79 and specificity = 0.9. Aside from force-tracking error, no other dexterity components correlated with antipsychotic medication. In patients, some dexterity components correlated with neurological soft signs, Positive and Negative Syndrome Scale (PANSS), or neuropsychological scores. This suggests differential cognitive contributions to these components. Cognitive remediation lead to significant improvement in PANSS, tracking error, and sequence recall (without change in medication). These findings show that multiple aspects of sensorimotor control contribute to impaired manual dexterity in schizophrenia. Only visuomotor precision was related to antipsychotic medication. Good diagnostic accuracy and responsiveness to treatment suggest that manual dexterity may represent a useful clinical marker in schizophrenia.